Towards Minimizing the Delay/Non-completion Rate of Research Master’s Degree in Ghana: ESL Students’ Perspective of the Challenges of Thesis Work - Rebecca Arthur; Daniel Arkoh Fenyi (Linguistics Initiative, 2023)
Extant literature confirms that the delay and non-completion of the thesis component of postgraduate studies remain a bane of postgraduate education. With the current spate of interest and enrolment into postgraduate studies in Ghana, and globally, it has become imperative to investigate the phenomenon and spotlight the contributing factors to the delay and non-completion of thesis so that students, supervisors, postgraduate faculties and departments, and all relevant stakeholders could pull efforts together to mitigate it. Through the purposive sampling method, the study recruited ten postgraduate students who have had varied experiences with thesis writing and are at different stages of completion. The data collection instrument was semi-structured interview. The conceptual framework adopted for the study was the Jiranck Dissertation Research Completion model (2010) and the data were analysed using the thematic analysis. The findings of the study revealed that three factors contribute to the delay and non-completion of thesis. These are; student-related factors, supervisor-related factors and institution-related factors. Based on the findings, it was recommended that postgraduate research institutions should design and develop plans and strategies to help their students complete the thesis within the stipulated period.